Resveratrol Improves the Energy Sensing and Glycolipid Metabolism of Blunt Snout Bream Megalobrama amblycephala Fed High-Carbohydrate Diets by Activating the AMPK–SIRT1–PGC-1α Network - Shi, Hua-Juan; Xu, Chao; Liu, Ming-Yang; Wang, Bing-Ke; Liu, Wen-Bin; Chen, Dan-Hong; Zhang, Li; Xu, Chen-Yuan; Li, Xiang-Fei (Frontiers in Physiology, 2018)
This study investigated the effects of resveratrol on the growth performance, energy sensing, glycolipid metabolism and glucose and insulin tolerance of blunt snout bream Megalobrama amblycephala fed high-carbohydrate diets. Fish (39.44 ± 0.06 g) were randomly fed three diets: a control diet (30% carbohydrate), a high-carbohydrate diet (HC, 41% carbohydrate), and the HC diet supplemented with 0.04% resveratrol (HCR) for 12 weeks. Fish fed the HC diet had significantly high values of nitrogen and energy retention efficiency, hepatosomatic index, intraperitoneal fat ratio, whole-body lipid content and intraperitoneal fat glycogen and lipid contents compared to the control group, but showed little difference with the HCR treatment. Liver and muscle lipid contents and plasma levels of glucose, glycated serum protein, advanced glycation end products and total cholesterol of fish fed the HC diet were significantly higher than those of the control group, whereas the opposite was found with resveratrol supplementation. Fish fed the HC diet obtained significantly low values of plasma insulin levels and hepatic adenosine monophosphate (AMP) contents and NAD+/NADH ratio compared to HCR treatment, but showed little difference with the control group. The opposite was found for hepatic adenosine triphosphate (ATP) contents and the ATP/AMP ratio. In addition, fish fed the HC diet showed significantly high transcriptions of glucose transporter 2 (GLUT2), glucose-6-phosphate dehydrogenase, glycogen synthase, fatty acid synthetase (FAS), acetyl-CoA carboxylase α (ACCα), peroxisome proliferator-activated receptor γ and PPARα compared to the control group, whereas the opposite was found for protein levels of AMP-activated protein kinase α (t-AMPKα), phosphorylated AMP-activated protein kinase α (p-AMPKα), Sirtuin-1 (SIRT1) and p-AMPKα/t-AMPKα ratio as well as the transcriptions of AMPKα1, AMPKα2, SIRT1, PPARγ coativator-1α (PGC-1α), phosphoenolpyruvate carboxykinase, fructose-1,6-biphosphatase (FBPase), glucose-6-phosphatase, carnitine palmitoyl transferase I (CPT I) and acyl-CoA oxidase. Resveratrol supplementation significantly up-regulated the protein levels of t-AMPK, p-AMPK and SIRT1, p-AMPK/t-AMPK ratio as well as the transcriptions of AMPKα1, AMPKα2, SIRT1, PGC-1α, GLUT2, FBPase and CPT I compared to HC group, while the opposite was found for sterol regulatory element-binding protein-1, FAS and ACCα. Furthermore, resveratrol improved glucose and insulin tolerance of fish fed the HC diet after glucose and insulin load.